Single-center experience with the ClotTriever BOLD catheter for deep vein thrombosis percutaneous mechanical thrombectomy of the lower extremity - De Marco Garcia, Lorena P. (Frontiers in Surgery, 2023)
Background The ClotTriever System is a percutaneous mechanical thrombectomy system used to treat deep vein thrombosis (DVT). The BOLD catheter is a newer compatible component with a modified coring element for which reported outcomes are limited. This retrospective study aims to assess the preliminary procedural safety and success data for patients treated with the BOLD catheter. Methods All consecutive patients with symptomatic lower extremity DVT who underwent thrombectomy with the BOLD catheter between 23 November 2021 and 26 June 2022 at a single center were included. Baseline and procedural characteristics were reported. The primary outcome, intraprocedural safety, was assessed by a chart review of recorded intraprocedural adverse events (AEs) or device malfunction. The secondary outcome, procedural success, was defined as ≥75% reduction in the total occlusion across treated venous segments. This was assessed by an interventionalist review of pre- and postprocedural venograms. Additional outcomes included length of postprocedural hospital stay and assessment of AEs at discharge and a 30-day follow-up visit. Results Eleven patient cases were reviewed. The median patient age was 65 years, the majority were women, and all were treated unilaterally. All procedures were completed in a single session without intraprocedural AEs or device malfunction. The median procedural blood loss was 50 ml. A review of pre- and postprocedural venograms showed that 35 venous segments were treated, including the femoral (n = 9), common femoral (n = 9), external iliac (n = 10), and common iliac (n = 7) veins. Procedural success was achieved in 10 patients (90.9%), and the median reduction rate in venous occlusion was 100%. The median length of postprocedural hospital stay was 1 day, and no AEs were noted at discharge (N = 11). One adverse event occurred among the eight patients who completed their follow-up visit. A patient with advanced-stage cancer and medication failure had a recurrent DVT 13 days postprocedure, which was not related to the device or procedure. Conclusions No safety concerns concerning the BOLD catheter were raised during the review of the cases included in this analysis, and the device was successful in reducing venous occlusion in patients with symptomatic proximal lower extremity DVT.